Understanding traditional and modern eating: the TEP10 framework - Gudrun Sproesser; Matthew B. Ruby; Naomi Arbit; Charity S. Akotia; Marle dos Santos Alvarenga; Rachana Bhangaokar; Isato Furumitsu; Xiaomeng Hu; Sumio Imada; Gülbanu Kaptan; Martha Kaufer-Horwitz; Usha Menon; et al. (BMC, 2019)
Abstract Across the world, there has been a movement from traditional to modern eating, including a movement of traditional eating patterns from their origin culture to new cultures, and the emergence of new foods and eating behaviors. This trend toward modern eating is of particular significance because traditional eating has been related to positive health outcomes and sustainability. Yet, there is no consensus on what constitutes traditional and modern eating. The present study provides a comprehensive compilation of the various facets that seem to make up traditional and modern eating. Specifically, 106 facets were mentioned in the previous literature and expert discussions, combining international and interdisciplinary perspectives. The present study provides a framework (the TEP10 framework) systematizing these 106 facets into two major dimensions, what and how people eat, and 12 subdimensions. Hence, focusing only on single facets of traditional and modern eating is an oversimplification of this complex phenomenon. Instead, the multidimensionality and interplay between different facets should be considered to gain a comprehensive understanding of the trends, consequences, and underlying factors of traditional and modern eating.